Intact Glucocorticoid Receptor Dimerization Is Deleterious in Trauma-Induced Impaired Fracture Healing - Hachemi, Yasmine; Rapp, Anna E.; Lee, Sooyeon; Dorn, Ann-Kristin; Krüger, Benjamin T.; Kaiser, Kathrin; Ignatius, Anita; Tuckermann, Jan (Frontiers in Immunology, 2021)
Following severe trauma, fracture healing is impaired because of overwhelming systemic and local inflammation. Glucocorticoids (GCs), acting via the glucocorticoid receptor (GR), influence fracture healing by modulating the trauma-induced immune response. GR dimerization-dependent gene regulation is essential for the anti-inflammatory effects of GC. Therefore, we investigated in a murine trauma model of combined femur fracture and thoracic trauma, whether effective GR dimerization influences the pathomechanisms of trauma-induced compromised fracture healing. To this end, we used mice with decreased GR dimerization ability (GRdim). The healing process was analyzed by cytokine/chemokine multiplex analysis, flow cytometry, gene-expression analysis, histomorphometry, micro-computed tomography, and biomechanical testing. We discovered that GRdim mice were protected from fracture healing impairment induced by the additional thorax trauma. In addition, GRdim mice did not display a systemic or local hyper-inflammation, which possibly contributed to improved fracture healing. Collectively and in contrast to previous studies describing the beneficial effects of intact GR dimerization in inflammatory models, we report here an adverse role of intact GR dimerization in trauma-induced compromised fracture healing.